ANALISIS TERJEMAHAN TINDAK TUTUR MEMUJI (COMPLIMENT) PADA SUBTITLE FILM TWILIGHT SERIES DAN KUALITAS TERJEMAHANNYA - Wahyudi Wahyudi; M.R. Nababan; Tri Wiratno (PRASASTI: Journal of Linguistics, 2017)
The aims of the study are to analyze the translations of compliment in subtitle film Twilight Series  between source text (English) and target text (Indonesian). To identify classifications of compliment in source text and target text, to identify shifting type of compliment, to identify the translations techniques, and to describe translation quality result in target text subtitle film Twilight Series.This study is a descriptive, qualitative research. Sources of the data are subtitle film Twilight Series in source text (English) and target text (Indonesian). The data are word, phrase, sentence, and clause forms which is contained compliment speech act discussed by informants to describe the translation quality. Techniques of collecting data are document analysis, and Forum Group discussion (FGD). Purposive sampling is applied in this research.Findings of this research show the followings. Classification form (reactive-unsolicited-direct-explicit) 1.5%, (reactive-unsolicited-indirect-implicit-presupposed) 1.5 %, (initiative-solicited-direct-explicit) 1.5 5%, (initiative-unsolicited-direct-explicit) 32.8%, (initiative-unsolicited-direct-implicit-presupposed) 12.5%, (initiative-unsolicited-direct-implicit-implied) 1.5%, (initiative-unsolicited-indirect-explicit) 1.5 %, (initiative-unsolicited-indirect-implicit-presupposed) 46.8 %. the translations techniques consist of establish equivalent, variation, reduction, literal, pure borrowing, linguistic compression, modulation, and discursive creation. Pragmatic Shifting type are meaning and classification form.The translation quality values score 2.75 for Accuracy, 2.94 for Acceptability, 3 point for Readability. The average value of translation quality of compliment speech act in subtitle film Twilight Series is 2.85, so it can be said that translation quality is good. Keywords : Translation, Compliment Speech Act, Classification Type, Translation Technique and Translation Quality.